2017
DOI: 10.3748/wjg.v23.i10.1816
|View full text |Cite
|
Sign up to set email alerts
|

miR-34a mediates oxaliplatin resistance of colorectal cancer cells by inhibiting macroautophagy via transforming growth factor-β/Smad4 pathway

Abstract: AIMTo investigate whether microRNA (miR)-34a mediates oxaliplatin (OXA) resistance of colorectal cancer (CRC) cells by inhibiting macroautophagy via the transforming growth factor (TGF)-β/Smad4 pathway.METHODSmiR-34a expression levels were detected in CRC tissues and CRC cell lines by quantitative real-time polymerase chain reaction. Computational search, functional luciferase assay and western blotting were used to demonstrate the downstream target of miR-34a in CRC cells. Cell viability was measured with Cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(83 citation statements)
references
References 26 publications
1
81
0
Order By: Relevance
“…Drug-specific mechanisms clustered into pathways, some of which were previously described. For example, TGFB1-dependent activation of the SMAD regulatory complex has been associated with oxaliplatin resistance (Mao et al, 2017;Sun et al, 2017) and hedgehog signaling has been linked to irinotecan resistance (Meng et al, 2015;Tripathi et al, 2014). Biosynthesis of heme and several phospholipid molecules were pathways uniquely associated with resistance to our nucleoside analogs.…”
Section: Crispr Screening Reveals Drug Resistance Genesmentioning
confidence: 99%
“…Drug-specific mechanisms clustered into pathways, some of which were previously described. For example, TGFB1-dependent activation of the SMAD regulatory complex has been associated with oxaliplatin resistance (Mao et al, 2017;Sun et al, 2017) and hedgehog signaling has been linked to irinotecan resistance (Meng et al, 2015;Tripathi et al, 2014). Biosynthesis of heme and several phospholipid molecules were pathways uniquely associated with resistance to our nucleoside analogs.…”
Section: Crispr Screening Reveals Drug Resistance Genesmentioning
confidence: 99%
“…Previous studies showed that miR-34a was down-regulated in multiple malignant tumors, CRC included. Sun et al [67] investigated the role of miR-34a in resistance to L-OHP chemotherapy on CRC cells. Thirty CRC patients that underwent potentially curative surgery and were treated with L-OHP based adjuvant chemotherapy were included in the study.…”
Section: Mirnas Predicting Treatment Response In Crcmentioning
confidence: 99%
“…Furthermore, transforming growth factor‐β (TGF‐β) signaling plays an important role in autophagy, the activation of which is mediated by the Smads. MiR‐34a sensitizes CRC cells to oxaliplatin via targeting the Smad4/TGF‐β pathway . MiR‐218 also sensitizes CRC cells to oxaliplatin.…”
Section: Micrornas Cell Death and Oxaliplatin Resistancementioning
confidence: 99%
“…MiR-34a sensitizes CRC cells to oxaliplatin via targeting the Smad4/TGF-β pathway. 38 MiR-218 also sensitizes CRC cells to oxaliplatin. It inhibits cytoprotective autophagy by targeting the YEATS domain containing 4 (YEATS4)-mediated oncogenic pathways.…”
Section: Micrornas Cell Death and Oxaliplatin Resistancementioning
confidence: 99%